Pediatric Primary Care Provider Perspectives on Universal Suicide Screening - Katie Plax; Edan Leshem; Sherry Dodd; Ruoyun Wang; Shannon Rook; Lauren Ericson; Andrew Solsrud (SAGE Publishing, 2024)
Introduction: Given the increase in youth mental health concerns, the American Academy of Pediatrics (AAP) recommends universal suicide screening for ages 12 and older, with positive screens followed by a brief suicide risk assessment. However, it is unclear how pediatric clinicians incorporate this recommendation into practice. Therefore, the objective of this qualitative study was to identify pediatric clinicians' current practice, attitudes, and barriers to implement the updated universal suicide screening recommendation in primary care. Methods: Community-based pediatric primary care providers (PCPs) in the St. Louis Metropolitan area who by self-report provide mental health care for patients participated. Participants completed a 30-minute semi-structured interview with invitations extended through an electronic listserv in a local Pediatric PCP Learning Collaborative. Interviews were transcribed and analyzed using consensual deductive and inductive approaches until data saturation. Results: Eighteen PCPs participated in the interviews. Interviews described themes related to acceptability of the recommendations, PCPs' current screening practices, and perceived barriers for implementing the recommendations. Overall, PCPs agreed with, but expressed hesitancy about, the recommendation. Frequently mentioned barriers to suicide screening included time, training, and inadequate access to resources for follow-up care for at-risk patients. Yet, PCPs were optimistic they could learn with support and were interested in working in this subject area through quality improvement interventions. Conclusions: PCPs agree with the AAP recommendation about suicide screening but need support to implement into practice. Specifically, PCPs need time sensitive strategies, resources, training, and practice change support to assist these efforts.